2020
DOI: 10.1007/s11010-020-03888-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of bone marrow stem cells on mitochondrial function and the alleviation of ARDS

Abstract: Mesenchymal stem cells (MSCs) can alleviate acute respiratory distress syndrome (ARDS), but the mechanisms involved are unclear, especially about their specific effects on cellular mitochondrial respiratory function. Thirty mice were allocated into the Control, LPS, and LPS + Bone marrow mesenchymal stem cell (BMSC) group (n = 10/group). Mouse alveolar epithelial cells (MLE-12) and macrophage cells (RAW264.7) were divided into the same groups. Pathological variation, inflammationrelated factors, reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These findings clarified the effectiveness of bMSCs cell therapy on LPS-induced EG degradation and implied that the related mechanism may be associated with inflammation regulation.bMSCs are known for their considerable immunomodulatory functions, a meta-analysis showed that bMSCs attenuated circulating inflammatory cytokine levels and protected against organ injury in animal studies [ 33 ]. Several laboratory studies have shown that MSCs reduce pulmonary edema by regulating calcium signaling pathways, and focal adhesion between ECs [ 19 , 40 ]. The modalities and targets of inflammation modulation of bMSCs in LPS-induced EG degradation and leakage are elucidated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings clarified the effectiveness of bMSCs cell therapy on LPS-induced EG degradation and implied that the related mechanism may be associated with inflammation regulation.bMSCs are known for their considerable immunomodulatory functions, a meta-analysis showed that bMSCs attenuated circulating inflammatory cytokine levels and protected against organ injury in animal studies [ 33 ]. Several laboratory studies have shown that MSCs reduce pulmonary edema by regulating calcium signaling pathways, and focal adhesion between ECs [ 19 , 40 ]. The modalities and targets of inflammation modulation of bMSCs in LPS-induced EG degradation and leakage are elucidated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They are rendered toxic as they damage lipids, proteins, and DNA and can represent themselves as damage-associated molecular patterns (DAMPs) that promote inflammation and tissue injury [89,90]. During lung infection, neutrophils generate large amounts of ROS via the NADPH oxidase (NOX) complex [91,92]. The activation of the NOX enzyme complex is the process by which bacteria cause excessive ROS production in neutrophils.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%